A family with Danon disease caused by a splice site mutation in LAMP2 that generates a truncated protein. Issue 3 (3rd February 2019) - Zhou, Nianwei; Cui, Jie; Zhao, Weipeng; Jiang, Yingying; Zhu, Wenqing; Tang, Lu; Li, Xuejie; Sun, Minmin; Pan, Cuizhen; Shu, Xianhong
Abstract: Background: Danon disease is an X‐linked dominant hereditary condition caused by mutations in the gene encoding lysosomal‐associated membrane protein 2 (LAMP2), leading to failure of lysosome binding to autophagosomes, accumulation of glycogen in the heart, and abnormal cardiac function. Methods: We describe identification of a mutation in LAMP2, c.741+1G>T, in a family with Danon disease by whole exome sequencing. Results: Pathology examination of patient skeletal muscle biopsy showed myogenic damage and autophagic vacuoles with sarcolemmal features (AVSF). Numerous autophagic vacuoles accumulated in muscle cells were detected by electron microscopy, indicating abnormal autophagy function. Conclusion: The mutation did not result in loss of mRNA exons; rather, a 6‐nucleotide (two‐codon) insertion, where the latter was a stop codon, leading to early termination of LAMP2 protein translation. The resulting truncated protein lacks an important transmembrane domain, which will impair lysosome/autophagosome fusion, damage autophagy function, and result in the clinical manifestations of Danon disease. Abstract : we found a new mutation site and pathogenic mechanism of the lamp2 gene. Our work illustrates the power of applying WES to identify gene mutations in genetic disorders.